Reconstructing Disability Rights Paradigm: Harmonizing Pancasila’s Humanity Principle within the Global Constitutionalism Trend - Zahwa Purwa Anggita (Universitas Negeri Semarang, 2025)
Global constitutionalism has fundamentally shifted the paradigm of disability rights from a charity-based medical model to a rights-based social model, as epitomized by the UN Convention on the Rights of Persons with Disabilities (CRPD). However, the domestication of these global norms in Indonesia often faces friction with local cultural interpretations that still view disability through a lens of pity. This paper aims to harmonize the global standards of the CRPD with the local philosophical foundation of Indonesia, specifically the Second Principle of Pancasila (Kemanusiaan yang Adil dan Beradab). Using a normative legal research method with conceptual and comparative approaches, this study analyzes the compatibility between the